Public-private partnership in cord blood banking. Issue 7645 (20th March 2008) - Fisk, Nicholas M; Atun, Rifat
Abstract : Demand for stem cells from cord blood is greater than supply. Nicholas Fisk and Rifat Atun examine the potential of Virgin's combination of personal and public banking to increase storage